Semantic Shifts and Intertext as Problems of Translation (while Translating Akhmatova) - Bednarczyk, Anna (Respectus Philologicus, 2004)
This paper aims at consideration of two poems by Anna Akhmatova: «Ты знаешь, я томлюсь в неволе ...» and its Polish translations by Adam Pomorski and by Gina Gieysztor, and «Уединение» and its translations by Eugenia Siemaszkiewicz and by Leopold Lewin.The main attention is concentrated on the reconstruction of the semantic level of the target text, including the translation shifts of the poetical images, and on the problem of the reconstruction of intertextual elements observed in the original.The analysis allows distinguishing the inherent translation methods and describing the character of the translation transformations observed in the texts.The paper emphasises the problem of change of the intertextual associations, the issue of acceptability of the original realities in another culture, and it claims that in some cases the intertextual context does not play an important role either in the process of translation or in its critical evaluations. The intertextual and extra-textual elements (including biographical ones) of the original are important for the full and clear understanding of the text, but they might be alien for the recipients of the translation who do not know the cultural context of the original.Therefore, preservation of the intertextual and extra-textual elements in the translation is not always obligatory. On the other hand, international intertextual elements, intrinsic to both sociocultural systems, must be reconstructed.